PROGRAM KETAHANAN PANGAN DANA DESA DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI DAN MENGURANGI KEMISKINAN DI KABUPATEN BIREUEN - Muhammad Rizal; Heri Gustami; Hakim Muttaqim; M. Saleh; Azka Rizkina (LPPM-UNIKI, 2025)
This study aims to analyze the role of food security programs funded through village fund allocations in realizing food security at the rural level in Bireuen Regency. Using a qualitative approach that emphasizes observing the natural conditions of the objects, the research informants consisted of three main groups: the Village Head, Village Facilitators, and the community. The results showed that the food security program funded by village funds has a significant level of effectiveness. The program has been proven to contribute to reducing poverty in Bireuen Regency by providing access to more affordable and nutritious food for those in need. Furthermore, the assistance provided by village facilitators is not only limited to the distribution of food aid, but also directed at increasing community capacity in managing resources and utilizing available opportunities to achieve long-term sustainability. The community's response, which tends to be positive, is an indicator that the food security program through village funds provides real benefits in improving the quality of life of the people of Bireuen Regency